Photocatalytic and Antibacterial Potential of Green Synthesized Silver Nanoparticles by Using Leaf Extract of Syzygium cumini - Arshad, M.; Qayyum, A.; Arshad, A.; Ahmad, S.; Sultan, A. (The Nucleus, 2016)
Silver nanoparticles were successfully synthesized by leaf extract of Syzygium cumini. The phytochemicals present in S. cumini leaf extract were used for stabilization and reducing agent for the synthesis of silver nanoparticles. The stabilization of silver nanoparticles with phytochemicals was justified using Fourier-transform infrared spectroscopy. Scanning electron microscopy was performed for the morphology of morphology of nanoparticles which showed the cabbage flower like structure. X-ray diffraction analysis showed that the size of synthesized nanoparticles was found as 12.13nm. Effect of temperature was observed by using thermo gravimetric analysis which revealed the thermal stability till 300oC. Antibacterial potential by a disc diffusion assay showed significant results. Photocatalytic activity of silver nanoparticles showed that gradual increases of degradation (%) of methyl orange dye occur with respect to time for 2 hrs in the interval of 10 minutes.